Treatment of Extraocular Infections (International Journal of Food and Nutritional Sciences, 2022)
Children, including newborns and infants, frequently struggle with extraocular infection. Rapid extraocular disease detection and treatment at the point of contact diminish ocular morbidity and visual impairment.Blindness, occasionally bilateral due to severe ophthalmianeonatorum, may occur if the proper therapy is not administered on time and the patient is not referred to eye care professionals. This review's primary goal is to provide working paediatricians and neonatologists with basic, succinct information regarding common extraocular illnesses that affect newborns and kids living in developing countries. Through this review, pediatricians—as the child's initial point of contact—might feel more secure and at ease handling ocular infections in children, especially those living in distant rural and tribal areas. A literature search was conducted by extracting pertinent publications from peer-reviewed journals, PUBMED, and Cochrane meta-analyses.